Impoliteness, pseudo-politeness, strategic politeness? On the nature of communicative behaviour in electoral debates - Fernández García, Francisco (Círculo de Lingüística Aplicada a la Comunicación, 2014)
This article analyses communicative behaviour in electoral debates, particularly with regard to the presence of elements of politeness or impoliteness. From both these questions, we develop two independent, albeit connected, lines of argument with the ultimate aim of discerning whether the features characterising politeness or impoliteness in debates are analogous to or, on the contrary, substantially different from those found in casual conversations. Our study has been conducted on the basis of our previous research and new data, and through a critical evaluation of the literature generated over the past few decades concerning both research into (im)politeness and into speaker behaviour in electoral debates. From this analysis, we conclude that both politeness and impolitenesss are genuine elements in debates, that is to say, debates are not radically unlike casual conversations, even if they do constitute a genre displaying a number of peculiarities arising from their public nature.